2008
DOI: 10.1007/s00586-008-0823-6
|View full text |Cite
|
Sign up to set email alerts
|

The association between prevalent neck pain and health-related quality of life: a cross-sectional analysis

Abstract: The aim of this study was to examine the association between grades of neck pain severity and health-related quality of life (HRQoL), using a populationbased, cross-sectional mailed survey. The literature suggests that physical and mental HRQoL is worse for individuals with neck pain compared to those without neck pain. However, the strength of the association varies across studies. Discrepancies in study results may be attributed to the use of different definitions and measures of neck pain and differences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 30 publications
2
38
1
2
Order By: Relevance
“…Regarding the relationship between neck pain and physical health-related QOL (HRQOL) in large population-based cohort studies, Nolet et al [67] reported that neck pain was associated with worse physical HRQOL, and Rezai et al [68] reported that neck pain was weakly associated with physical HRQOL and that comorbid conditions accounted for most of the association between neck pain and physical HRQOL.…”
Section: Association With Locomotive Syndromementioning
confidence: 99%
“…Regarding the relationship between neck pain and physical health-related QOL (HRQOL) in large population-based cohort studies, Nolet et al [67] reported that neck pain was associated with worse physical HRQOL, and Rezai et al [68] reported that neck pain was weakly associated with physical HRQOL and that comorbid conditions accounted for most of the association between neck pain and physical HRQOL.…”
Section: Association With Locomotive Syndromementioning
confidence: 99%
“…21 The questionnaire has been shown to be reliable and valid in various populations with good internal consistency (α coefficients, N.85). 9,20,22,23 Exercise. Exercise frequency was measured with a question asking the average number of days per week participating in a minimum of 30 minutes of exercise.…”
Section: Category 2 Variables That May Be On the Causal Pathwaymentioning
confidence: 99%
“…The Comorbidity Questionnaire has been shown to have good test-retest reliability (intraclass correlation coefficient, 0.93) and adequate face, concurrent, and convergent validity. 9,10 Outcome Troublesome neck pain in the past 6 months was measured with the Chronic Pain Questionnaire at 6 and 12 months of follow-up. The questionnaire is used to grade neck pain and its related disability into 5 ordered categories.…”
Section: Exposurementioning
confidence: 99%
“…[2] Neck pain and LBP are associated with significant disability and comorbidities, which can significantly affect quality of life. [2,3] Upper limb disability is a common musculoskeletal condition and its prevalence has been reported as 20% to 70% in the working population. [4,5] Upper limb disability can occur because of many clinical conditions such as neck problems.…”
Section: Introductionmentioning
confidence: 99%